Investigation of charm-quark hadronization into baryons in hadronic collisions with ALICE - Cho Jaeyoon (EPJ Web of Conferences)
A comprehensive investigation into charm-baryon production provides insight into understanding charm-quark hadronization process. In this contribution, the charm-quark hadronization mechanism is discussed in terms of the production yield ratio between charm hadron species measured by ALICE Collaboration. Measurements of Λc+, ∑c0,+ +, Ξc0,+ and Ωc0 in pp collisions, Λc+ and Ξc0 in p–Pb collisions are presented, together with the Λc+ measurement in larger collision systems, Pb–Pb collisions. Furthermore, the charm-quark hadronization mechanism is discussed based on the fragmentation fractions computed for pp and p–Pb collisions. A preliminary result on ∑c0,+ + measurement with Run 3 data is also presented.